+0  
 
0
44
1
avatar

Simplify (sqrt(12) - sqrt(27))/6 * sqrt(3) * sqrt(4).

 Dec 1, 2019
 #1
avatar
0

Simplify the following:
(sqrt(12) - sqrt(27))/(6 sqrt(3) sqrt(4))

sqrt(4) = sqrt(2^2) = 2:


(sqrt(12) - sqrt(27))/(6 sqrt(3)×2)

sqrt(27) = sqrt(3^3) = 3 sqrt(3):


(sqrt(12) - 3 sqrt(3))/(6 sqrt(3)×2)

sqrt(12) = sqrt(2^2×3) = 2 sqrt(3):


(2 sqrt(3) - 3 sqrt(3))/(6 sqrt(3)×2)

2 sqrt(3) - 3 sqrt(3) = -sqrt(3):


(-sqrt(3))/(6 sqrt(3)×2)

 (sqrt(3))/(sqrt(3))×(-1)/(6×2) = (-1)/(6×2):
(-1)/(6×2)

 

- 1 / 12

 Dec 1, 2019

16 Online Users

avatar